Cross-Cultural Communication in Sino-US Co-Production Films (2010—2024) - Wang, Kun; Srijinda, Prakaikavin (Journal of Cultural Analysis and Social Change, 2025)
This study aims to evaluate the market performance and cross-cultural communication strategies of Sino-American co-produced films, with the objective of identifying cultural factors that influence audience reception and transnational cinematic success between China and the United States. The research adopts a qualitative approach, analyzing 24 Sino-American co-productions released between 2010 and 2024. Data were collected from authoritative movie databases including IMDb, Box Office Mojo, Rotten Tomatoes, and Douban. The analysis utilized the High- and Low-Context Theory as a theoretical framework, with textual analysis of film content, genres, ratings, and narrative structures. This was supplemented by comparative assessments of audience reviews and professional critiques. Findings reveal both convergence and divergence in the box office performance of Sino-American co-productions across regions. Significant cultural differences were observed in creative direction, theme selection, marketing tactics, and media engagement strategies. These factors collectively shaped the effectiveness of cross-cultural communication and audience engagement. Cultural differences play a pivotal role in shaping the success and reception of co-productions in global markets. Addressing these differences through creative and strategic collaboration is essential to achieving cultural resonance and market adaptability. The study offers practical recommendations to enhance the cultural and commercial effectiveness of Sino-American co-productions: (1) Foster collaboration between leading creators from both nations; (2) Promote cultural exchange programs to raise cultural awareness; (3) Enhance cultural integration benefits; (4) Refine cooperative production models; (5) Jointly develop intellectual properties (IP) to increase brand and market value; and (6) Establish a digital communication matrix to improve global promotional impact. These findings contribute to strengthening the international competitiveness of Chinese films and advancing effective cross-cultural cinematic exchange.